SPECIFIC FEATURES OF DEVELOPMENT OF CREATIVITY OF BACHELOR STUDENTS OF PEDAGOGICAL EDUCATION - Tolipova Ozodaxon Ikromovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article describes the content of the educational process, the signs of creativity, the stages and stages of development of creativity, aimed at the development of creative competence in university students. The importance of a set of skills and effective methods and tools that allow teachers to organize creative activities is also highlighted.